Mothers' beliefs about children's learning in Hong Kong and the United States: Implications for mothers' child-based worth. (September 2013) - Ng, Florrie Fei-Yin; Pomerantz, Eva M.; Lam, Shui-fong
Chinese and American mothers' beliefs about children's learning and parents' role in it were examined using notions salient in Chinese culture. Mothers from Hong Kong ( n = 66) and the United States ( n = 69) indicated their endorsement of the ideas that children's learning reflects children's morality, and parents' support of children's learning reflects parents' love and duty. Mothers also reported on the extent to which their worth is based on children's performance. Chinese (vs. American) mothers believed more that children's learning reflects morality and parents' support of children's learning reflects love; these differences accounted for their feelings of worth being more dependent on children's performance. Chinese (vs. American) mothers believed less that parents' support is a duty.